Kriteria Desain Dinding Penahan Pada Tanah Campuran - Apriani, Dyah Wahyu; Hadid, Muhammad (Politeknik Negeri Semarang, 2019)
Retaining wall is one of the reinforcing techniques used to control soil movement. Reinforcement with retaining walls is relatively expensive so an efficient design is needed. Unfortunately, the guidelines for planning a retaining wall are limited. Analysis of design criteria was carried out on silt clay soil taken in the area of the Karang Joang Kalimantan Institute of Technology (ITK) area based on the dimension guide given by Hardiyatmo (2010) and Nakazawa, et al (1980) for safe slope height based on the type of retaining wall. The minimum criteria for cantilever type retaining walls with a slope height of 2-3 meters is the width of the TOE (A) = B / 3 meters, the base width retaining wall (B) = minimum of 0.7 H meters, the width of the upper wall (C) = 0.2 meters and wall thickness (D) = H / 10-H / 12 meters, while for slopes with a height of 4- 5 meters the safe dimension range is TOE (A) width = A / 3, slope width (B) is designed to be a minimum of 0.9 H meters, width of the wall (C) = minimum 0.2 meters and wall thickness (D) = H / 10-H / 12 meters. Gravity retaining wall has design criteria for slopes as high as 2-3 meters of A = D / 2-D meters, B is taken to a minimum of 0.7 H meters, a minimum C value of 0.3 m and D of H / 8 - H / 6 meters for slopes with a height of 2-3 meters, meanwhile for slopes with a height of 4-5 meters, B to a minimum of 0.9 H meters, with a value of A = D / 2-D meters, the C value is designed to be a minimum of 0.3 meters and D = H / 8 - H / 6 meters.